2004
DOI: 10.1118/1.1812608
|View full text |Cite
|
Sign up to set email alerts
|

On the use of EPID‐based implanted marker tracking for 4D radiotherapy

Abstract: Four-dimensional (4D) radiotherapy delivery to dynamically moving tumors requires a real-time signal of the tumor position as a function of time so that the radiation beam can continuously track the tumor during the respiration cycle. The aim of this study was to develop and evaluate an electronic portal imaging device (EPID)-based marker-tracking system that can be used for real-time tumor targeting, or 4D radiotherapy. Three gold cylinders, 3 mm in length and 1 mm in diameter, were implanted in a dynamic lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 38 publications
0
73
0
Order By: Relevance
“…Multiple images can be taken to monitor patient movement and to readjust patient position between fields if such movement occurs. However, for applications involving continuous tracking of patient movement, such as for respiratory motion tracking or gating using an internal surrogate, (22) images have to be taken at a much higher frequency (>10/s) to reduce potential time delays (23) . The total dose could be significant, and optimal technical settings should be used in such an application.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple images can be taken to monitor patient movement and to readjust patient position between fields if such movement occurs. However, for applications involving continuous tracking of patient movement, such as for respiratory motion tracking or gating using an internal surrogate, (22) images have to be taken at a much higher frequency (>10/s) to reduce potential time delays (23) . The total dose could be significant, and optimal technical settings should be used in such an application.…”
Section: Discussionmentioning
confidence: 99%
“…The time taken to acquire a volume of data, t vol , is proportional to the product of the imaging depth (ID), the number of lines (L), and the number of frames (F). To track organ motion due to respiration in real-time, assuming a breathing cycle of 3-5 seconds, we require a volume acquisition rate, 1/t vol , of ~10 Hz (Keall et al 2004). To achieve this volume acquisition rate without restricting the field of view to a few cubic centimetres, spatial resolution has to be sacrificed using techniques such as parallel beam forming in receive mode (Smith et al 1991) or by reducing the spatial sampling frequency (so as to reduce L or F).…”
Section: Introductionmentioning
confidence: 99%
“…Of more concern is the fact that the beam is triggered by the breathing signal and often there is no real-time verification of the actual tumour position during beam-on time. However, it has been shown that it is achievable using implanted markers (Berbeco et al, 2005b;Keall et al, 2004). Another approach, to be discussed now, is tracking the tumour during irradiation and correcting for it in real-time (Keall et al, 2001;Murphy, 2004).…”
Section: Dynamic Compensation For Intra-fractional Tumour Movementmentioning
confidence: 99%